Hydrometallurgy : fundamentals and applications - Free, Michael (Hoboken, New Jersey : Wiley : TMS, 2013)
As the first book to compile the fundamentals, applications, reference information and analytical tools on the topic, Hydrometallurgy presents a condensed collection of information that can be used to improve the efficiency and effectiveness with which metals are extracted, recovered, manufactured, and utilized in aqueous media in technically viable and reliable, environmentally responsible, and economically feasible ways. Suitable for students and researchers, this college-level overview addresses Fundamentals of Chemical Metallurgy in Aqueous Media, Speciation and Phase Diagrams, Rate.
9.2 United States Environmental Policy Issues9.3 Metal Removal and Remediation Issues; References; Problems; Chapter 10: Process Design Principles; 10.1 Determination of Overall Objectives; 10.2 Determination of Basic Flow Sheet Segments; 10.3 Survey of Specific Segment Options; 10.4 Overall Flow Sheet Synthesis; 10.5 Procurement of Additional Information; 10.6 Selected Industrial Flow Sheet Examples; References; Problem; Chapter 11: General Engineering Economics; 11.1 The Effects of Time and Interest; 11.2 Return on Investment (ROI); 11.3 Cost Estimation.
11.4 Discounted Cash Flow Economic Analysis.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed September 23, 2013).
Keywords: Hydrometallurgy; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; TECHNOLOGY & ENGINEERING -- Metallurgy; Hydrometallurgy; Electronic books; Electronic books